Preferensi Wisatawan Terhadap Destinasi Wisata Pantai Camplong Kabupaten Sampang - Ika Nur Wahyuni; Novi Diana Badrut Tamami (LPPM Universitas Trunojoyo Madura, 2021)
The business competition of service industry recently is very competitive especially in tourism sector, which involves various economic sectors. Tourist’s desire visits a tourist destination influenced by tourist preferences. The purpose of this study are: (1) to determine the characteristics of Camplong beach in Sampang Regency’svisitors, (2) knowing tourist’s preferences for attributes and attribute’s level in tourist visitation to Camplong beach in Sampang Regency. The research method uses descriptive and conjoint analyze. The results show that the characteristics of tourists are mostly dominated by school students or college students with average of age in 15-65 years old, this category visitors usually travels with their friends or family whose unmarried status with income of Rp 1,000,000.00. The attributes chosen by tourists are tourism activities which is motorcycle tracks, motorcycle transportation, restaurant accommodations, beach facilities such as photo spots and souvenir types, include clothes.